Physiological response to a breed evaluation field test in Icelandic horses - G.J. Stefánsdóttir (Animal, 2014)
This study examined the response in terms of heart rate (HR), respiratory rate (RR), haematocrit (Htc), rectal temperature (RT), and some plasma variables in Icelandic horses of different sexes and ages performing the riding assessment in a breed evaluation field test (BEFT). The study was conducted in Iceland on 266 horses (180 mares and 86 stallions, divided into four age groups; 4, 5, 6 and ⩾7 years old). RT and RR were recorded and blood samples were taken before the warm-up and after the riding assessment. Horse HR, velocity and distance were recorded during the warm-up, the riding assessment and a 5-min recovery period. The distance covered in the BEFT was 2.9±0.4 km (range: 1.8 to 3.8 km, n=248), the duration was 9:37±1:22 min:s (range: 5:07 to 15:32 min:s, n=260) and the average speed was 17.8±1.4 km/h (range: 13.2 to 21.3 km/h, n=248). Average HR was 184±13 b.p.m. (range: 138 to 210 b.p.m., n=102) and peak HR 224±9 b.p.m. (range: 195 to 238 b.p.m., n=102), and 36% of the BEFT was performed at HR ⩾200 b.p.m. Post-exercise plasma lactate concentration (Lac) was 18.0±6.5 mmol/l (range: 2.1 to 34.4 mmol/l, n=266), and there was an increase in total plasma protein, plasma creatine kinase and aspartate amino transferase concentration, as well as RR, RT and Htc. Stallions covered a longer total distance (in the warm-up and BEFT) (P<0.05), at a faster speed during BEFT (P<0.001) than mares and had higher Htc and lower HR and post-exercise Lac values. There were few effects of age, but the 4- and 5-year-old horses had lower Htc than older horses and 4-year-old horses had higher post-exercise RR than older horses, although they were ridden for a shorter distance, shorter duration and at lower peak velocity (P<0.1). The results showed that the riding assessment in the BEFT is a high-intensity exercise. The results also showed that aerobic fitness was higher in stallions and that age had a limited effect on the physiological response. It is suggested that these results should be used as a guide for the development of training programmes and fitness tests in Icelandic horses that would improve both performance and welfare of the horse.